2010
DOI: 10.1101/gad.1839510
|View full text |Cite
|
Sign up to set email alerts
|

Spred1, a negative regulator of Ras–MAPK–ERK, is enriched in CNS germinal zones, dampens NSC proliferation, and maintains ventricular zone structure

Abstract: Neural stem cells (NSCs) have great potential for self-renewal, which must be tightly regulated to generate appropriate cell numbers during development and to prevent tumor formation. The Ras-MAPK-ERK pathway affects mitogen-stimulated proliferation, and negative regulators are likely to be important for keeping selfrenewal in check. Sprouty-related protein with an EVH1 domain (Spred1) is a recently discovered negative Ras-MAPK-ERK regulator linked to a neurofibromatosis 1 (NF-1)-like human syndrome; however, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 48 publications
2
58
0
Order By: Relevance
“…Spred1 and Spred2 are known to be expressed by Müller glia, and levels of Spred1 are influenced by retinal degeneration (Roesch et al, 2008(Roesch et al, , 2012. Interestingly, Spred1 is enriched in neural stem cells in the rodent ventricular zone and acts to suppress proliferation (Phoenix and Temple, 2010). Collectively, our data suggest that activation of GCR may upregulate transcription of Spred1 to dampen MAPK signaling in Müller glia in damaged retinas, but not in FGF2-treated retinas in the absence of damage.…”
Section: Discussionmentioning
confidence: 62%
“…Spred1 and Spred2 are known to be expressed by Müller glia, and levels of Spred1 are influenced by retinal degeneration (Roesch et al, 2008(Roesch et al, , 2012. Interestingly, Spred1 is enriched in neural stem cells in the rodent ventricular zone and acts to suppress proliferation (Phoenix and Temple, 2010). Collectively, our data suggest that activation of GCR may upregulate transcription of Spred1 to dampen MAPK signaling in Müller glia in damaged retinas, but not in FGF2-treated retinas in the absence of damage.…”
Section: Discussionmentioning
confidence: 62%
“…10,11 Similarly to neurofibromin, SPRED1 is a negative regulator of RAS-MAPK signaling. 12 Before the cloning of the NF1 gene two other related disorders, Watson syndrome (WS) and NF1-Noonan syndrome (NFNS), had been described clinically, both have been shown to be caused by NF1 mutations. Watson 13 described autosomal dominant inheritance of PS, multiple CALS spots and intelligence at the lower end of the normal range.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, SPRED1 knockdown studies in mice underlined its importance for brain development and supported the hypothesis of its involvement in vesicle transport (26,37).…”
mentioning
confidence: 68%
“…SPRED1 has been shown to be expressed predominantly in the brain (21,26) and to be enriched in the central nervous system, where it mediates cortical development, neural stem cell proliferation, and vesicular trafficking (26,37). Recently, it has been shown that germ line loss-of-function mutations of SPRED1 cause the neurofibromatosis type 1-like Legius syndrome, associated with café-au-lait spots, facial abnormalities, and behavioral and learning problems (31,(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%